Konsep Manusia dan Pendidikan dalam Pandangan Syed Muhammad Naquib Al-Attas: Catatan Awal - Muhammad Arsyad (SIASAT, 2019)
In determining human concepts and Islamic education that are appropriate, comprehensive, ideal and integral, it becomes a moral responsibility for every education expert to develop theories as the paradigm of Islamic education that he formulated, as practiced by the popular education figure, Syed Muhammad Naquib Al-Attas. For Al-Attas, humans are creatures consisting of two elements, namely physical and spiritual. What is very important to develop according to him is the spiritual side, because if the spiritual side is established and knows the nature of life's purpose, the greater the potential to become a civilized human being. So that it will provide instructions on education, both in theory and practice. So it is expected that an expert in exploring and developing the concept of education must first study and examine the nature of human beings and their environment, this will affect the pattern of solving the educational problems they face. For Al-Attas the proper term for Islamic education is ta'dib not tarbiyyah or ta'lim because according to al-Attas the structure of the concept of ta'dib includes the elements of science (ilm), instruction (ta'lim) and good coaching (tarbyiyah). The term ta'dib is not only limited to cognitive aspects, but also includes spiritual education.